Video imaging study of ethanol- gasoline blends fuel spray - Wan Mohd Hazwan, Wan Ariff (2012)
This is a study of result image spray produce from different ratio of gasoline and ethanol mixtures. This study is to determine how the spray forms during combustion while using different ratio of gasoline and ethanol. The spray characteristics of this studies includes the spray angle, sprays penetration, and spray wide area. Three mixtures was prepared that is E0, E50 and E100. After completed the experimental setup, each sample of experiment was tested to produce the spray pattern by using the pump pressure and the process was recorded by using the DSLR camera. Two different pressures were 3 bars and 5 bars to compare of spray pattern. Parameters the result obtains are then compared with the previous researching result get.